VANILLIN EXTRACTED FROM PROSO MILLET AND BARNYARD MILLET INDUCE APOPTOSIS IN HT-29 AND MCF-7 CELL LINE THROUGH MITOCHONDRIA MEDIATED PATHWAY - Ramadoss, Deepa Priya; Sivalingam, Nageswaran (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main aim of the study was to investigate the bioactive compound vanillin extracted from proso millet (compound 1), and barnyard millet (compound 2) induces apoptotic cell death and whether it is mediated through mitochondrial pathway in HT-29 and MCF-7 cell line. Methods: The cells were treated with 250 Î¼g/ml and 1000 Î¼g/ml concentration of extracted vanillin for 48 hrs. Cytochrome c release and expression level of pro-apoptotic protein Bax and caspase-9 were detected by western blot analysis. Results: The results reveal that extracted compounds increased the release of cytochrome c and upregulating the expression of Bax and caspase-9 as concentration increases in a dose-dependent manner. Conclusion: The study suggests that the vanillin compound extracted from these millets induces apoptotic cell death through a mitochondria-dependent pathway.